2023
DOI: 10.1002/adhm.202302056
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzing Generation and Stabilization of Oxygen Vacancies on CeO2−x Nanorods by Pt Nanoclusters as Nanozymes for Catalytic Therapy

Jiankang Zhang,
Yu Yang,
Fengmin Qin
et al.

Abstract: Although CeO2 nanomaterials have been widely explored as nanozymes for catalytic therapy, they still suffer from relatively low activities. Herein, we report the catalyzing generation and stabilization of oxygen vacancies on CeO2 nanorods by Pt nanoclusters via H2 gas reduction under mild temperature (350 °C) to obtain Pt/CeO2‐x, which can serve as a highly efficient nanozyme for catalytic cancer therapy. The deposited Pt on CeO2 by the atomic layer deposition technique not only can serve as the catalyst to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…As shown in Fig. 2C, it was obviously observed that some characteristic peaks appeared for CeO 2 , consistent with the reported results [39]. However, compared with CeO 2 , it maintained almost the same crystallinity for Ce@P, demonstrating that PDA coating did not change the crystallization structure in this case.…”
Section: Preparation and Physicochemical Propertiessupporting
confidence: 89%
“…As shown in Fig. 2C, it was obviously observed that some characteristic peaks appeared for CeO 2 , consistent with the reported results [39]. However, compared with CeO 2 , it maintained almost the same crystallinity for Ce@P, demonstrating that PDA coating did not change the crystallization structure in this case.…”
Section: Preparation and Physicochemical Propertiessupporting
confidence: 89%
“…ROS-induced apoptosis and cellular energy conversion are closely correlated with the change of mitochondrial membrane potential (MMP, ΔΨm) and dysfunction. , The 5,5′,6,6′-tetrachloro-1,1′-3,3′-tetraethyl-benzimidazolylcarbocyanine iodide (JC-1) probe, which could actively interact with respiring mitochondria, , was applied to monitor the MMP of 4T1 cells after treatment. JC-1 aggregates in the matrix of mitochondria when the MMP is high and forms “J-aggregates” with red fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Three kinds of O species, namely surface lattice oxygen (O l ), oxygen vacancy (O v ), and chemisorbed oxygen (O ads ), are presented. O l , O v , and O ads are located at 529.85 eV, 531.29 eV, and 532.35 eV, respectively [36]. The O l species accounts for 72.97% of the total surface oxygen, and O v and O ads account for 17.15% and 9.88%, respectively.…”
Section: Synthesis and Characterization Of Comno X Nanoflowersmentioning
confidence: 99%